The Insulin-like Growth Factor System and Colorectal Cancer - Nikola Gligorijević; Zorana Dobrijević; Miloš Šunderić; Dragana Robajac; Danilo Četić; Ana Penezić; Goran Miljuš; Olgica Nedić (Life, 2022)
Insulin-like growth factors (IGFs) are peptides which exert mitogenic, endocrine and cytokine activities. Together with their receptors, binding proteins and associated molecules, they participate in numerous pathophysiological processes, including cancer development. Colorectal cancer (CRC) is a disease with high incidence and mortality rates worldwide, whose etiology usually represents a combination of the environmental and genetic factors. IGFs are most often increased in CRC, enabling excessive autocrine/paracrine stimulation of the cell growth. Overexpression or increased activation/accessibility of IGF receptors is a coinciding step which transmits IGF-related signals. A number of molecules and biochemical mechanisms exert modulatory effects shaping the final outcome of the IGF-stimulated processes, frequently leading to neoplastic transformation in the case of irreparable disbalance. The IGF system and related molecules and pathways which participate in the development of CRC are the focus of this review.